A Frequency, Risk Factors, and Outcome of Acute Kidney Injury in Idiopathic Childhood Nephrotic Syndrome: A Systematic Review: Systematic review of Acute kidney injury in childhood nephrotic syndrome (Pakistan Journal of Kidney Diseases, 2025)
Background and Objectives:Idiopathic nephrotic syndrome is a common glomerular disease with a good prognosis in the long term. However, the development of acute kidney injury may complicate the disease course. This systematic review was conducted to evaluate the frequency, risk factors and outcome of AKI in children with idiopathic nephrotic syndrome.Methods:PubMed, EMBASE, and CENTRAL were systematically searched from January 1974 to July 2024 for retrospective and prospective observational studies. The systematic review was prospectively registered with PROSPERO and written in compliance with PRISMA guidelines. The quality assessment tool was used to evaluate the quality of included studies.Results:Out of 271 identified studies, 14 were included in the systematic review. Most studies were retrospective in design. The most common risk factors for acute kidney injury in children were infections (sepsis, spontaneous bacterial peritonitis, pneumonia, and urinary tract infections) and nephrotoxic drug exposure (e.g., nephrotoxic antibiotics, renin-angiotensin modifiers, methylprednisolone, and calcineurin inhibitors). Recovery from AKI occurred in 48–100% of cases, while chronic kidney disease development ranged from 0 - 41.2% and a maximum reported mortality rate of 23%. The quality assessment through NHLBI rated 85% studies as good.Conclusion:Acute kidney injury is a relatively frequent and serious complication in children with nephrotic syndrome, often associated with infections and nephrotoxic drug exposure. This systematic review, conducted using a structured approach highlights the need of preventive strategies and further research in this vulnerable population.
Keywords: 1. Nephrotic syndrome 2. Acute kidney injury and 3. Outcome